Tanyproctus (Tanyproctus) arher (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini), a new species from the Socotra Island, Yemen - Bezděk, Aleš; Sehnal, Richard; Král, David (Zootaxa, 2013)
Tanyproctus (Tanyproctus) arher Bezděk, Sehnal & Král, new species, is described from Socotra Island (Yemen), based on external morphology including male genitalia.